A pyrazine‐bridged trimer of oxo‐centered triruthenium–carbonyl clusters and the supramolecular assembly built from multiple noncovalent contacts. Issue 12 (6th December 2020) - Daicho, Keita; Ozawa, Yoshiki; Sugimoto, Kunihisa; Abe, Masaaki
Abstract: The crystal structure of a new pyrazine‐bridged trimer of oxo‐centered triruthenium–carbonyl clusters formulated as [Ru3 O(EtCOO)6 (CO)(pyrazine)]2 [Ru3 O(EtCOO)6 (CO)(μ‐pyrazine)2 ] (1 ) has been unequivocally determined by single‐crystal X‐ray diffraction (SC‐XRD) analysis at 100 K. A supramolecular cyclic assembly of two trimers was formed via intermolecular CO⋯CO contacts, which is further assembled into a three‐dimensional orthogonal layer‐by‐layer stack via hydrogen bonds. Abstract : The crystal structure of a pyrazine‐bridged trimer of triruthenium–carbonyl clusters has been unambiguously determined by single‐crystal X‐ray diffraction analysis. The formation of a supramolecular cyclic assembly of two trimers, which is supported by intermolecular noncovalent CO⋯CO contacts, is observed in the solid state.